Evaluation of covered blocks with steel fibers reinforced mortar. - C. Seco (Revista INGENIERÍA UC, 2015)
The principal aim of this work was to evaluate the compressive strenght of blocks covered with mortar of cement reinforced with fiber of steel DRAMIXr, and to compare them with blocks covered with traditional mortar in order to determine the influence of the fibers on the mixture resistance. The investigation was of descriptive type with a field design, based in the tests results realized at the Materials and Tests Laboratory of the Carabobo's University Faculty of Engineering. Three mixtures were elaborated, with traditional mortar and with fiber percentages of 0,5 % and 1 % respectively, then 20 clay blocks were covered with every mixture and were evaluated to compression. The obtained results demonstrated that the fiber improves the compressive strenght as the added percentage is major, demonstrating better results the blocks recovered with 1 % of added fiber mixture.